Sentença parcial de mérito: a admissibilidade do fracionamento do julgado na atual sistemática processual como meio de concretização da garantia constitucional à razoável duração do processo - Oliveira, Alessandra Prôa Greenhalgh de (2014)
Apathy of the Brazilian State in the execution of his power / the duty to resolve intersubjective conflicts has as a direct consequence of the social discredit the judiciary, a fact confirmed by the data of the survey conducted by the Institute for Applied Economic Research (IPEA). Thus, it remained evident the urgent need to find solutions to the problem of delays in the judiciary. In the postmodern view of the procedural instrumentality, law is both guided by the fundamental constitutional rights, such as concretizing its precepts, whose magnum scope to social peace with justice. His instrument function is characterized by the achievement of substantive law with fairness and timeliness to ensure the effectiveness and usefulness of the decisions handed down. However, for the effective exercise of this function prolific, procedural law requires the establishment of mechanisms to ensure the speed of the procedural motion, as guaranteed by the Constitution. Focused this innate and before changing the concept of sentence introduced by Law 11.232/05 deficiency, the possibility arises from the breakup of the trial by the utterance of partial judgment on the merits, as a means of providing the citizen the desired speed. This institute has proved fully viable in the current systematic procedural, being advocated as a means of making permanent the constitutional principle providing a more reasonable length of proceedings. The study in this project, based on bibliographic research in books and articles by renowned jurists, along with analysis of legislative amendments to the Code of Civil Procedure and national case law, concluded that besides allowed by current law, the Office of the partial sentence merit was more effective in ensuring a speedy adjudication, providing a greater likelihood of effectiveness and usefulness of the sentence, being extremely beneficial to those who seek the tutelage Judiciary.